Digital Teaching Materials Explanation Text Critical Thinking for Junior High School/Middle School - Sujali; Yusida Gloriani; Dede Endang Mascita (International Journal of Educational Research Excellence (IJERE), 2024)
The objective of this research is to develop digital teaching materials for explanatory texts designed for students in junior high school. The following issues represent the primary challenges associated with this research: (1) What is the optimal design of digital teaching materials for critical thinking explanatory texts for junior high school/MTs? (2) What are the outcomes of the implementation of digital teaching materials for critical thinking explanatory texts for junior high school/MTs? This research employs the research and development method (R&D) with the ADDIE model (analysis, design, development, implementation, evaluation). The research methodology comprises the following steps: analysis of needs, design of digital teaching materials for explanatory text, development of digital teaching materials for explanatory text, implementation of digital teaching materials for explanatory text, and evaluation of digital teaching materials for explanatory text. In this study, data were collected from the results of validation questionnaires completed by experts in learning models, media, and implementation in learning, as well as from the actual implementation of the learning model. The data were subjected to descriptive analysis using the Likert scale and paired sample t-test. The validation test conducted with material experts yielded a score of 3.5, while the test with media experts returned a score of 3.9. The validation test with Indonesian language teachers also produced a score of 3.9. The implementation of digital teaching materials for critical thinking explanatory texts for junior high school/MTs students prompted positive responses from the students, resulting in a score of 3.5. The findings of this study indicate that digital teaching materials for critical thinking explanations for junior high school/MTs students satisfy the criteria for feasibility in terms of their potential use as a learning model by teachers of Indonesian language subjects on explanatory text material for junior high school/MTs class VIII students.